Analisis Kerentanan Pesisir Akibat Kenaikan Muka Air Laut di Kota Semarang Menggunakan Sistem Informasi Geografis (SIG) - Dwi, Andika Niqa; Ananto, Aji; Budi, Sanjoto Tjaturahono (Geo-Image, 2018)
The purpose of this research is to assess the vulnerability of coastal area due to sea level rise in Semarang City. Assessing vulnerability is done by calculating coastal vulnerability index with 6 parameters, ie geomorphology, coastal slope, coastline change, sea level rise, tides, and sea waves. The results of coastal susceptibility indexes are classified into grade level of potential hazards / vulnerabilities. This study resulted in coastal vulnerability level of Semarang City classified in medium and high class. Areas with class of potential hazard / vulnerability are classified into 5 village namely Tugurejo, Tambakharjo, Tawangsari, Panggung Lor, and Bandarharjo. As for the class is high there are 9 villages namely Mangkang Kulon, Mangunharjo, Mangkang Wetan, Randugarut, Karanganyar, Tanjung Mas, Terboyo Kulon, Terboyo Wetan and Trimulyo. Parameters that affect coastal vulnerability in Semarang are coastline, geomorphology and sea level rise. On the parameter of coastline change shows negative changes in the form of abrasion, thus reducing the area of land. Geomorphological parameters of coastal areas of Semarang City belong to high vulnerability. Meanwhile, the topography in the coastal city of Semarang is classified as sloping so it is very vulnerable to sea level rise.